Functional Heterogeneity in CD4+ T Cell Responses Against a Bacterial Pathogen - Milam, Ashley Viehmann; Allen, Paul M. (Frontiers in Immunology, 2015)
To investigate how CD4+ T cells function against a bacterial pathogen, we generated a Listeria monocytogenes-specific CD4+ T cell model. In this system, two TCRtg mouse lines, LLO56 and LLO118 recognize the same immunodominant epitope (LLO190-205) of Listeria monocytogenes and have identical in vitro responses. However, in vivo LLO56 and LLO118 display vastly different responses during both primary and secondary infection. LLO118 dominates in the primary response and in providing CD8 T cell help. LLO56 predominates in the secondary response. We have also shown that both specific (TCR-mediated) and nonspecific stimuli (bypassing the TCR) elicit distinct responses from the two transgenics, leading us to conclude that the strength of self-pMHC signaling during development tightly dictates the cell’s future response in the periphery. Herein, we review our findings in this transfer system, focusing on the contribution of the immunomodulatory molecule CD5 and the importance of self-interaction in peripheral maintenance of the cell. We also discuss the manner in which individual TCR affinities to foreign and self-pMHC contribute to the outcome of an immune response; our assertion is that there exists a spectrum of possible T cell responses to recognition of cognate antigen during infection, adding immense diversity to the immune system’s response to pathogens.